MAKNA SLOGAN IKLAN PRODUK MINUMAN ICHITAN: KAJIAN SEMANTIK - Syandria Laila Putri (STKIP Pesisir Selatan, 2026)
The meaning in advertising slogans plays an important role in influencing consumer perceptions of a product. Slogans with good, appropriate, and meaningful language will be able to attract consumers to buy the product. This study aims to describe the types of meaning contained in the advertising slogans of all variants of Ichitan beverage products. Data was obtained from Ichitan beverage advertising slogans found on PT Ichi Tan's social media, both in the form of images and product videos. The method used in this study was qualitative descriptive with a focus on semantic meaning. The research stages began with observing Ichitan advertisements and noting the slogans that appeared in the advertisements. Next, the collected data was analyzed, classified according to meaning type, and concluded. The study shows that out of fourteen Ichitan beverage variants, there are six slogans with connotative meanings and eight slogans with grammatical meanings. Overall, connotative meanings refer to additional meanings that have positive connotations and contain taste values, while grammatical meanings tend to refer to the state of experiencing something; fresh, aroma, fruit, exciting, energetic, relaxed, different, and addictive. The slogans in Ichitan beverage advertisements not only present meanings that can influence consumers, but also build an image as a product that prioritizes authentic taste, high quality, and creative marketing strategies.